Negative electrode binder, negative electrode sheet and lithium ion battery

By using a specific composition of the negative electrode binder in lithium-ion batteries, the problem of poor storage performance of the negative electrode binder in high humidity environments is solved, and the low-temperature capacity retention, rate performance and corrosion resistance of the battery are significantly improved.

CN118956306BActive Publication Date: 2025-02-18SHENZHEN HAODYNE TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411449095.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-02-18
Estimated Expiration
2044-10-17

AI Technical Summary

Technical Problem

The storage performance of negative electrode binders in high humidity environments is poor, resulting in the low-temperature cycling and rate performance of lithium-ion batteries being affected.

Method used

A negative electrode binder is used, which comprises a specific first unsaturated carboxylic acid monomer unit and a specific proportion of the first vinyl monomer, an aliphatic conjugated unsaturated monomer, a first unsaturated carboxylic The acid monomer and the first unsaturated ester monomer work together to improve corrosion resistance.

Benefits of technology

In high humidity environments, the negative electrode binder exhibits excellent storage stability and corrosion resistance, significantly improving the low-temperature capacity retention, rate performance and corrosion resistance of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention provides a negative electrode binder, a negative electrode sheet and a lithium ion battery, wherein the negative electrode binder comprises a first vinyl monomer unit, an aliphatic conjugated unsaturated monomer unit, a first unsaturated carboxylic acid monomer unit and a first unsaturated ester monomer unit; the first unsaturated carboxylic acid monomer unit comprises two or more unsaturated carboxylic acid monomer units; the glass transition temperature of the negative electrode binder is ‑50 to 80° C.; the swelling rate of the negative electrode binder is 50% to 300%. The negative electrode binder can improve the low temperature cycle performance, rate performance and anti-corrosion performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a negative electrode binder, in particular to a negative electrode binder, a negative electrode sheet and a lithium ion battery, belonging to the field of secondary batteries. Background Art

[0002] Lithium-ion batteries have become the main power source of choice for modern portable electronic devices, electric vehicles and energy storage systems due to their advantages such as high energy density, long cycle life and low self-discharge rate. There are also higher requirements for their electrical properties including low-temperature cycle performance, rate performance and storage performance.

[0003] At present, technicians in this field have done a lot of work to improve the electrochemical performance of batteries, improve the working efficiency and reliability of lithium-ion batteries, and meet the needs of most application scenarios. At present, there have been studies to improve the low-temperature performance and rate performance of batteries by optimizing electrolyte formula, improving electrode materials, optimizing electrode structure, and improving binder composition. Among them, the negative electrode binder improves the adhesion between the negative electrode active layer and the negative electrode current collector, ensures the structural stability and conductivity of the negative electrode sheet, and reduces the probability of lithium dendrite precipitation, thereby improving the low-temperature cycle performance and rate performance of lithium-ion batteries.

[0004] However, the storage stability of the negative electrode binder is worrying, especially in a high humidity environment, where it faces the storage performance problem of mold growth, thus affecting the degree of optimization of battery performance.

[0005] Therefore, how to overcome the storage performance defects of negative electrode binders in high humidity environments is a technical problem that needs to be solved urgently by those skilled in the art. Summary of the invention

[0006] The present invention provides a negative electrode binder, which can show excellent storage stability and strong corrosion resistance in a high humidity environment, and thus helps to improve the low-temperature capacity retention rate and rate performance of a modified ion battery.

[0007] The present invention also provides a negative electrode sheet comprising the negative electrode binder, which has excellent capacity retention and microbial corrosion resistance at low temperatures and can significantly improve the low temperature performance, rate performance and corrosion resistance of the battery.

[0008] The present invention also provides a lithium ion battery comprising the above-mentioned negative electrode binder or negative electrode sheet, which has high low-temperature capacity retention rate, good anti-corrosion performance, and good rate performance.

[0009] In the first aspect, the present invention provides a negative electrode binder, which includes a first vinyl monomer unit, an aliphatic conjugated unsaturated monomer unit, a first unsaturated carboxylic acid monomer unit, and a first unsaturated ester monomer unit; the first unsaturated carboxylic acid monomer unit includes two or more unsaturated carboxylic acid monomer units; the glass transition temperature of the negative electrode binder is -50~80℃; and the swelling rate of the negative electrode binder is 50%~300%.

[0010] In the negative electrode binder as described above, wherein the weight ratio of the first vinyl monomer unit, the aliphatic conjugated unsaturated monomer unit, the first unsaturated carboxylic acid monomer unit, and the first unsaturated ester monomer unit is 0.1-50:0.1-50:0.1-20:0.1-100.

[0011] In the negative electrode binder as described above, the first unsaturated carboxylic acid monomer unit includes a normal acid monomer unit and a functional acid monomer unit.

[0012] In the negative electrode binder as described above, the weight ratio of the conventional acidic monomer unit to the functional acidic monomer unit is 0.1-19.9:0.1-19.9.

[0013] In the negative electrode binder as described above, wherein the negative electrode binder further comprises a first monomer unit;

[0014] The first monomer unit includes at least one of a (meth)acrylonitrile monomer unit, a vinyl pyrrolidone monomer unit, a butenyl nitrile monomer unit, and a vinyl ether monomer unit.

[0015] In the negative electrode binder as described above, the weight ratio of the first monomer unit to the first vinyl-based monomer unit is 0.1-50:0.1-50.

[0016] In the negative electrode binder as described above, wherein the negative electrode binder further comprises a second vinyl monomer unit, a second unsaturated ester monomer unit and an unsaturated functional monomer unit;

[0017] The weight ratio of the first vinyl monomer unit, the second vinyl monomer unit, the second unsaturated ester monomer unit, and the unsaturated functional monomer unit is 0.1-50:20-100:20-100:0.1-20.

[0018] In the negative electrode binder as described above, wherein the negative electrode binder further comprises a second monomer unit;

[0019] The second monomer units include (meth)acrylonitrile units, vinyl pyrrolidone units, butenyl nitrile units, vinyl ether units, methacrylamide units, diacetone acrylamide units, ethyl acetoacetate methacrylate units, N-hydroxymethyl methacrylamide units, N,N-dimethylacrylamide units, N-methyl-2-acrylamide units, N-tert-butylacrylamide units, 2-acrylamido-2-methylpropanesulfonic acid units, dipropylene glycol diacrylate units, triethylene glycol di(meth)acrylate units, polyethylene glycol units. At least one of polyethylene glycol (200) diacrylate units, polyethylene glycol (300) diacrylate units, polyethylene glycol (400) diacrylate units, polypropylene glycol (400) diacrylate units, tetraethylene glycol dimethacrylate units, polyethylene glycol (200) dimethacrylate units, polyethylene glycol (400) dimethacrylate units, trimethylolpropane triacrylate units, 2-(ethoxy)trimethylolpropane triacrylate units, pentaerythritol triacrylate units, and pentaerythritol tetraacrylate units.

[0020] In a second aspect, the present invention provides a negative electrode sheet, wherein the negative electrode sheet comprises the negative electrode binder as described above.

[0021] In a third aspect, the present invention provides a lithium ion battery, wherein the lithium ion battery comprises the negative electrode binder or the negative electrode sheet as described above.

[0022] The present invention provides a negative electrode binder, which contains a specific first unsaturated carboxylic acid monomer unit, and a synergistic effect of a first vinyl monomer unit, an aliphatic conjugated unsaturated monomer unit, a first unsaturated carboxylic acid monomer unit, and a first unsaturated ester monomer unit in a specific ratio. The negative electrode binder has excellent anti-corrosion performance in a high humidity environment and is beneficial to significantly improving the rate performance and low-temperature cycle performance of a lithium ion battery. DETAILED DESCRIPTION

[0023] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] In the first aspect, the present invention provides a negative electrode binder, which includes a first vinyl monomer unit, an aliphatic conjugated unsaturated monomer unit, a first unsaturated carboxylic acid monomer unit, and a first unsaturated ester monomer unit; the first unsaturated carboxylic acid monomer unit includes two or more unsaturated carboxylic acid monomer units; the glass transition temperature of the negative electrode binder is -50~80℃; and the swelling rate of the negative electrode binder is 50%~300%.

[0025] In the present invention, as known to those skilled in the art, the monomer unit in the above polymer means: in a polymer obtained by polymerization of a certain monomer compound, the corresponding unit of the monomer compound in the polymer. For example, the first vinyl monomer unit means the unit corresponding to the first vinyl monomer in a polymer obtained by polymerization of the first vinyl monomer.

[0026] In the negative electrode binder, the weight ratio of the first vinyl monomer unit, the aliphatic conjugated unsaturated monomer unit, the first unsaturated carboxylic acid monomer unit, and the first unsaturated ester monomer unit is 0.1-50:0.1-50:0.1-20:0.1-100.

[0027] The first unsaturated carboxylic acid monomer units include conventional acid monomer units and functional acid monomer units, and the weight ratio of the conventional acid monomer units to the functional acid monomer units is 0.1-19.9:0.1-19.9.

[0028] The negative electrode binder further includes a first monomer unit; the first monomer unit includes at least one of a (meth)acrylonitrile monomer unit, a vinyl pyrrolidone monomer unit, a butenyl nitrile monomer unit, and a vinyl ether monomer unit.

[0029] The weight ratio of the first monomer unit to the first vinyl-based monomer unit is 0.1-50:0.1-50.

[0030] The negative electrode binder also includes a second vinyl monomer unit, a second unsaturated ester monomer unit and an unsaturated functional monomer unit; the weight ratio of the first vinyl monomer unit, the second vinyl monomer unit, the second unsaturated ester monomer unit and the unsaturated functional monomer unit is 0.1-50:20-100:20-100:0.1-20.

[0031] The negative electrode binder also includes a second monomer unit; the second monomer unit includes a (meth) acrylonitrile unit, a vinyl pyrrolidone unit, a butenyl nitrile unit, a vinyl ether unit, a methacrylamide unit, a diacetone acrylamide unit, an ethyl acetoacetate methacrylate unit, an N-hydroxymethyl methacrylamide unit, an N,N-dimethylacrylamide unit, an N-methyl-2-acrylamide unit, an N-tert-butylacrylamide unit, a 2-acrylamido-2-methylpropanesulfonic acid unit, a dipropylene glycol diacrylate unit, and a triethylene glycol di(meth)acrylate unit. At least one of the following units: polyethylene glycol (200) diacrylate units, polyethylene glycol (300) diacrylate units, polyethylene glycol (400) diacrylate units, polypropylene glycol (400) diacrylate units, tetraethylene glycol dimethacrylate units, polyethylene glycol (200) dimethacrylate units, polyethylene glycol (400) dimethacrylate units, trimethylolpropane triacrylate units, 2-(ethoxy)trimethylolpropane triacrylate units, pentaerythritol triacrylate units, and pentaerythritol tetraacrylate units.

[0032] In the present invention, the first polymer includes a first vinyl monomer unit, an aliphatic conjugated unsaturated monomer unit, a first unsaturated carboxylic acid monomer unit, and a first unsaturated ester monomer unit, and the weight ratio of the first vinyl monomer unit, the aliphatic conjugated unsaturated monomer unit, the first unsaturated carboxylic acid monomer unit, and the first unsaturated ester monomer unit is 0.1-50: 0.1-50: 0.1-20: 0.1-100.

[0033] Specifically, as an optional embodiment, in the first polymer, the first vinyl monomer unit includes at least one of a styrene unit, an α-methylstyrene unit, a vinyltoluene unit, a 2-vinylnaphthalene unit, a methylvinylnaphthalene unit, a vinylanthracene unit, and a methylvinylanthracene unit.

[0034] The aliphatic conjugated unsaturated monomer unit may include at least one of a 1,3-butadiene unit, a 1,3-pentadiene unit, a 2-methyl-1,3-butadiene unit, a 1,3-cyclopentadiene unit, and a 1,3-hexadiene unit.

[0035] The first unsaturated ester monomer unit may include at least one of a methyl (meth)acrylate unit, an ethyl (meth)acrylate unit, an isobutyl acrylate unit, a butyl (meth)acrylate unit, a 2-isooctyl (meth)acrylate unit, a lauryl (meth)acrylate unit, a octadecyl (meth)acrylate unit, a behenyl (meth)acrylate unit, a caprolactone acrylate unit, and a benzyl acrylate unit.

[0036] According to the present invention, the first unsaturated carboxylic acid monomer unit includes two or more unsaturated carboxylic acid monomer units. Specifically, the first unsaturated carboxylic acid monomer unit includes a conventional acidic monomer unit and a functional acidic monomer unit.

[0037] The conventional acidic monomer units include at least one of acrylic acid or anhydride units, methacrylic acid or anhydride units, fumaric acid or anhydride units, maleic acid or anhydride units, itaconic acid or anhydride units, and citraconic acid or anhydride units;

[0038] The functional acidic monomer unit includes at least one of sorbic acid or its derivative unit and dehydroacetic acid or its derivative unit.

[0039] The negative electrode binder of the present invention not only has good anti-corrosion performance, but also can effectively improve the rate performance of the battery and the capacity retention rate at low temperature. The inventor speculates that the reason may be: on the one hand, in the first polymer of the negative electrode binder provided by the present invention, the first unsaturated carboxylic acid monomer unit includes a special conventional acid monomer unit and a functional acid monomer unit, which cooperate with each other and form a polymer with other monomer units (first vinyl monomer unit, aliphatic conjugated unsaturated monomer unit, first unsaturated ester monomer unit), and the above monomer units cooperate with each other in a special ratio, and finally form a negative electrode binder with antifungal effect; on the other hand, the negative electrode binder also has excellent adhesion and flexibility, so the negative electrode active material and the conductive agent are more closely connected, and even if they are in an electrolyte environment for a long time, the negative electrode active layer will not fall off, which is beneficial to improve the rate performance and low temperature cycle performance of the battery.

[0040] Furthermore, preferably controlling the mass ratio of each monomer unit in the first polymer can further improve the low temperature performance of the negative electrode binder, thereby improving the low temperature capacity of the lithium ion battery. Specifically, the weight ratio of the first vinyl monomer unit, the aliphatic conjugated unsaturated monomer unit, the first unsaturated carboxylic acid monomer unit, and the first unsaturated ester monomer unit is 5-40:2-40:1-18:1-60.

[0041] In a specific embodiment, in the first polymer, the mass ratio of the conventional acidic monomer unit to the functional acidic monomer unit is controlled to be 0.1-19.9:0.1-19.9, preferably 0.1-10:0.1-10. This is beneficial to further improve the anti-corrosion performance of the negative electrode binder and facilitate the storage of the battery in a more severe humidity environment.

[0042] Furthermore, the inventors found that, preferably, the first polymer also includes a first monomer unit; the first monomer unit includes at least one of a (meth) acrylonitrile monomer unit, a vinyl pyrrolidone monomer unit, a butenyl nitrile monomer unit, and a vinyl ether monomer unit, and the weight ratio of the first monomer unit to the first vinyl monomer unit is 0.1 to 50: 0.1 to 50. At this time, the improvement of the anti-corrosion performance of the negative electrode binder and the low-temperature cycle performance of the battery is more significant.

[0043] In a specific embodiment, specifically, the negative electrode binder provided by the present invention may include a first polymer located inside and a second polymer located on the surface of the first polymer; the second polymer is chemically bonded to the first polymer, and / or the second polymer is physically bonded to the surface of the first polymer.

[0044] The second polymer includes a second vinyl monomer unit, a second unsaturated ester monomer unit and an unsaturated functional monomer unit; the weight ratio of the first vinyl monomer unit, the second vinyl monomer unit, the second unsaturated ester monomer unit and the unsaturated functional monomer unit is 0.1-50:20-100:20-100:0.1-20.

[0045] Furthermore, the ratio between the monomer units in the second polymer can be preferably controlled to improve the anti-corrosion performance, rate performance and low-temperature cycle performance of the negative electrode binder. For example, the weight ratio of the first vinyl monomer unit, the second vinyl monomer unit, the second unsaturated ester monomer unit, and the unsaturated functional monomer unit is 5 to 40: 20 to 70: 20 to 70: 0.1 to 10. It is further preferred that the weight ratio of the first vinyl monomer unit, the second vinyl monomer unit, the second unsaturated ester monomer unit, and the unsaturated functional monomer unit is 5 to 30: 20 to 50: 20 to 60: 0.1 to 8.

[0046] Furthermore, the glass transition temperature of the negative electrode binder of the present invention can be controlled to be -50~80°C to ensure that the polymer chain segments have a high mobility, so that the viscosity of the negative electrode binder is higher, meeting a wider temperature requirement, preventing particle shedding and electrode stratification, and improving low-temperature cycle performance. Specifically, the glass transition temperature of the negative electrode binder can be controlled to be -50~80°C by adjusting the type and mass ratio of the synthetic raw materials for preparing the negative electrode binder, so as to adapt well to the operating temperature of the lithium-ion battery. Preferably, the glass transition temperature of the negative electrode binder is -30~60°C. At this time, it is very beneficial to further improve the bonding performance of the negative electrode binder.

[0047] In addition, the second polymer further comprises a second monomer unit, and the weight ratio of the second monomer unit to the second vinyl monomer unit is 1-20:20-100.

[0048] The second monomer unit in the second polymer specifically includes but is not limited to (meth)acrylonitrile unit, vinyl pyrrolidone unit, butenyl nitrile unit, vinyl ether unit, methacrylamide unit, diacetone acrylamide unit, ethyl acetoacetate methacrylate unit, N-hydroxymethyl methacrylamide unit, N,N-dimethylacrylamide unit, N-methyl-2-acrylamide unit, N-tert-butylacrylamide unit, 2-acrylamido-2-methylpropanesulfonic acid unit, dipropylene glycol diacrylate unit, triethylene glycol di(meth)acrylate unit. At least one of the following units: polyethylene glycol (200) diacrylate unit, polyethylene glycol (300) diacrylate unit, polyethylene glycol (400) diacrylate unit, polypropylene glycol (400) diacrylate unit, tetraethylene glycol dimethacrylate unit, polyethylene glycol (200) dimethacrylate unit, polyethylene glycol (400) dimethacrylate unit, trimethylolpropane triacrylate unit, 2-(ethoxy)trimethylolpropane triacrylate unit, pentaerythritol triacrylate unit, and pentaerythritol tetraacrylate unit. Taking polyethylene glycol (200) diacrylate as an example, polyethylene glycol (200) diacrylate refers to a polymer of polyethylene glycol and diacrylate having an average molecular weight of 200 Daltons.

[0049] In another specific embodiment, in the above-mentioned second polymer, the second vinyl monomer unit includes at least one of a styrene unit, an α-methylstyrene unit, a vinyltoluene unit, a 2-vinylnaphthalene unit, a styrenated phenol unit, a methylvinylnaphthalene unit, a 6-vinyl-2-naphthol unit, a vinylanthracene unit, and a methylvinylanthracene unit.

[0050] The second unsaturated ester monomer unit can be selected from at least one of methyl (meth)acrylate unit, ethyl (meth)acrylate unit, isobutyl acrylate unit, butyl (meth)acrylate unit, 2-isooctyl (meth)acrylate unit, lauryl (meth)acrylate unit, octadecyl (meth)acrylate unit, behenyl (meth)acrylate unit, caprolactone acrylate unit, and benzyl acrylate unit.

[0051] The unsaturated functional monomer unit may include at least one of a sorbic acid unit or a salt thereof, and a dehydroacetic acid unit or a salt thereof.

[0052] When the second polymer contains the above-mentioned monomer units, the mutual synergistic effect between the monomer units not only enhances the affinity to the electrolyte, but also increases the solubility of lithium ions and reduces the obstacles to lithium ion transmission, which is beneficial to improving the rate performance and low-temperature cycle performance of the battery.

[0053] Specifically, by controlling the mass ratio of the first polymer to the second polymer to be 100:(0.01-50), the anti-corrosion performance of the negative electrode binder, as well as the low temperature capacity retention rate and rate performance of the battery can be further improved. Preferably, the mass ratio of the first polymer to the second polymer is 100:(0.01-20).

[0054] In the present invention, preferably, the swelling rate of the negative electrode binder is 50% to 300%, more preferably 80% to 250%. In this case, it is beneficial to further improve the rate performance of the battery. Specifically, it can be achieved by adjusting the mass ratio of the first polymer and the second polymer in the negative electrode binder, and their respective compositions.

[0055] The present invention does not strictly limit the preparation method of the negative electrode binder. For example, the following preparation method can be used:

[0056] (1) adding a first polymer synthesis raw material, performing a mixing and a heating, adding a first initiator to react, and cooling to obtain an intermediate;

[0057] Specifically, the synthetic raw materials of the first polymer include 0.1 to 50 parts of a first vinyl monomer, 0.1 to 50 parts of an aliphatic conjugated unsaturated monomer, 0.1 to 20 parts of a first unsaturated carboxylic acid monomer, and 0.1 to 100 parts of a first unsaturated ester monomer.

[0058] Wherein, the first initiator includes one or more of sodium persulfate, ammonium persulfate, potassium persulfate, tert-butyl hydroperoxide, azobisisobutyronitrile, benzoyl peroxide / sucrose, tert-butyl hydroperoxide / rongalite, tert-butyl hydroperoxide / sodium metabisulfite, benzoyl peroxide / N,N-dimethylaniline, ammonium persulfate / sodium bisulfite, potassium persulfate / sodium bisulfite, hydrogen peroxide / tartaric acid, hydrogen peroxide / rongalite, ammonium persulfate / ferrous sulfate, hydrogen peroxide / ferrous sulfate, benzoyl peroxide / N,N-diethylaniline, benzoyl peroxide / ferrous pyrophosphate, potassium persulfate / silver nitrate, persulfate / thiol, cumene hydroperoxide / ferrous chloride, potassium persulfate / ferrous chloride, hydrogen peroxide / ferrous chloride, cumene hydroperoxide / tetraethyleneimine, and the reaction temperature is 50-99°C.

[0059] (2) After mixing the intermediate and the synthetic raw material of the second polymer, a second initiator is added and reacted at 50 to 99° C. to obtain the negative electrode binder of the present invention.

[0060] In a specific embodiment, the synthetic raw materials of the second polymer include 20 to 100 parts by mass of a second vinyl monomer, 20 to 100 parts by mass of a second unsaturated ester monomer, and 0.1 to 20 parts by mass of an unsaturated functional monomer.

[0061] The second initiator may be the same as the first initiator.

[0062] In a second aspect, the present invention further provides a negative electrode sheet, comprising the negative electrode binder of the first aspect, which can be used as a negative electrode of a battery to significantly improve the low temperature performance, corrosion resistance and rate performance of the battery.

[0063] The negative electrode sheet of the present invention specifically comprises a negative electrode current collector and a negative electrode active layer formed of a negative electrode active material and arranged on the surface of the negative electrode current collector.

[0064] When preparing the negative electrode sheet, the negative electrode active material, the conductive agent, and the negative electrode binder can be dispersed in an appropriate amount of deionized water, and fully stirred and mixed to form a uniform negative electrode slurry; the negative electrode slurry is evenly coated on the negative electrode current collector, and the negative electrode sheet is obtained after drying, rolling and slitting. In a specific embodiment, the negative electrode active layer includes 70 to 99 wt% of the negative electrode active material, 0.5 to 15 wt% of the conductive agent, and 0.5 to 15 wt% of the negative electrode binder according to the mass percentage, and further includes 80 to 98 wt% of the negative electrode active material, 1 to 10 wt% of the conductive agent, and 1 to 10 wt% of the negative electrode binder.

[0065] Among them, the material of the negative electrode current collector layer can be at least one of copper foil, nickel foam, and copper foam; the conductive agent can be selected from at least one of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, and graphene.

[0066] In a third aspect, the present invention further provides a lithium ion battery, comprising the negative electrode binder of the first aspect or the negative electrode sheet of the second aspect. Therefore, the lithium ion battery of the present invention not only has good anti-corrosion performance, which is beneficial to battery storage, but also has excellent rate performance and low temperature cycle performance.

[0067] It is conceivable that the lithium-ion battery of the present invention includes, in addition to the negative electrode sheet, a positive electrode sheet, an electrolyte and a separator.

[0068] The present invention does not strictly limit the positive electrode active material in the positive electrode sheet, and can be a positive electrode active material commonly used in lithium-ion batteries, such as at least one composite oxide of lithium and metals of cobalt, manganese, nickel and combinations thereof. Specifically, it can be at least one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, nickel-cobalt-manganese ternary material, nickel-cobalt-aluminum ternary material, lithium iron phosphate (LFP), lithium nickel manganese oxide, lithium-rich manganese-based material, etc.

[0069] The present invention does not strictly limit the negative electrode active material in the negative electrode sheet, and can be at least one of the negative electrode active materials commonly used in lithium-ion batteries, such as graphite, hard carbon, soft carbon, mesophase carbon microbeads, silicon-based negative electrode materials (mainly including silicon oxide, silicon-carbon negative electrode), tin-based negative electrode materials (mainly including tin, tin alloy), etc.

[0070] The present invention does not strictly limit the selection of the electrolyte, and may include one or more of the solvents commonly used in lithium-ion battery electrolytes, and the electrolyte lithium salts commonly used in lithium-ion electrolytes. For example, the solvent may be ethylene carbonate, propylene carbonate, butylene carbonate, fluoroethylene carbonate (FEC), dimethyl carbonate (DMC), diethyl carbonate (DEC), difluoroethylene carbonate (DFEC), dipropyl carbonate, ethyl methyl carbonate (EMC), ethyl acetate, ethyl propionate, propyl acetate, propyl propionate, sulfolane, γ-butyrolactone, etc.; the lithium salt may be, for example, one or more of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium bis(trifluoromethylsulfonyl)imide (LiTFSI).

[0071] The present invention does not strictly limit the material selection of the diaphragm, which can be a diaphragm material commonly used in lithium-ion batteries, such as a polypropylene diaphragm (PP), a polyethylene diaphragm (PE), a polypropylene / polyethylene double-layer composite film (PP / PE), a polyimide electrospinning diaphragm (PI), a polypropylene / polyethylene / polypropylene three-layer composite film (PP / PE / PP), a cellulose non-woven fabric diaphragm, or a diaphragm with a ceramic coating.

[0072] When preparing lithium-ion batteries, the positive electrode sheet, separator and negative electrode sheet are wound or stacked to obtain a bare cell, and the bare cell is packaged in a pre-stamped aluminum-plastic film bag. After the packaged battery is dried at 85°C, the electrolyte is injected into the dry battery, and the battery is placed, formed and sealed for the second time to complete the preparation of the lithium-ion battery.

[0073] Example 1

[0074] The first polymer synthesis raw material of this embodiment includes the following components in parts by mass:

[0075] First vinyl monomer: 15 parts styrene, 4 parts vinyl toluene

[0076] Aliphatic conjugated unsaturated monomer: 1,3-pentadiene 12 parts

[0077] Conventional acidic monomer: 10 parts of methacrylic anhydride

[0078] Functional acid monomer: 5 parts of sorbic acid

[0079] The first unsaturated ester monomer: 16 parts of methyl acrylate

[0080] The second polymer synthesis raw material of this embodiment includes the following components in parts by mass:

[0081] Second vinyl monomer: 50 parts of styrene,

[0082] Second unsaturated ester monomer: 30 parts of methyl acrylate

[0083] Unsaturated functional monomer: 10 parts of sorbic acid.

[0084] The method for preparing the negative electrode binder of this embodiment comprises the following steps:

[0085] 1) adding the synthetic raw materials of the first polymer, mixing once and adding azobisisobutyronitrile to react at 60° C., and cooling to obtain an intermediate;

[0086] 2) After mixing the above intermediate and the synthetic raw material of the second polymer, ammonium persulfate was added and reacted at 50° C. to obtain the negative electrode binder of this embodiment. The mass ratio of the first polymer to the second polymer was 5:1.

[0087] Example 2

[0088] The first polymer synthesis raw material of this embodiment includes the following components in parts by mass:

[0089] First vinyl monomer: 40 parts of methylvinylnaphthalene, 5 parts of α-methylstyrene

[0090] Aliphatic conjugated unsaturated monomer: 20 parts of 1,3-hexadiene

[0091] Conventional acidic monomer: 5 parts of fumaric acid

[0092] Functional acid monomer: 5 parts of dehydroacetic acid

[0093] First monomer: 15 parts of butene nitrile

[0094] The first unsaturated ester monomer: 30 parts of caprolactone acrylate

[0095] The second polymer synthesis raw material of this embodiment includes the following components in parts by mass:

[0096] Second vinyl monomer: 30 parts of methyl vinyl naphthalene,

[0097] The second unsaturated ester monomer: 70 parts of (meth) acrylate

[0098] Unsaturated functional monomer: 5 parts of sorbic acid.

[0099] The preparation method of this embodiment is basically the same as that of Embodiment 1, except that, in the negative electrode binder, the mass ratio of the first polymer to the second polymer is 5:2.

[0100] Example 3

[0101] The first polymer synthesis raw material of this embodiment includes the following components in parts by mass:

[0102] The first vinyl monomer: 10 parts of methylvinyl anthracene

[0103] Aliphatic conjugated unsaturated monomer: 1,3-butadiene 50 parts

[0104] Conventional acidic monomer: 15 parts of maleic anhydride

[0105] Functional acid monomer: 2 parts of sorbic acid

[0106] First monomer: 28 parts of (meth)acrylonitrile

[0107] The first unsaturated ester monomer: 76 parts of isobutyl acrylate

[0108] The second polymer synthesis raw material of this embodiment includes the following components in parts by mass:

[0109] Second vinyl monomer: 78 parts of methylvinyl anthracene,

[0110] Second unsaturated ester monomer: 19 parts of 2-isooctyl acrylate

[0111] Unsaturated functional monomer: 20 parts of sorbic acid

[0112] Second monomer: 17 parts of N-methyl-2-acrylamide.

[0113] The preparation method of this embodiment is basically the same as that of Embodiment 1, except that, in the negative electrode binder, the mass ratio of the first polymer to the second polymer is 10:1.

[0114] Example 4

[0115] The first polymer synthesis raw material of this embodiment includes the following components in parts by mass:

[0116] The first vinyl monomer: 47 parts of α-methylstyrene

[0117] Aliphatic conjugated unsaturated monomer: 5 parts of 1,3-cyclopentadiene

[0118] Conventional acidic monomer: 7 parts of itaconic anhydride

[0119] Functional acid monomer: 13 parts of dehydroacetic acid

[0120] First monomer: 40 parts of (meth)acrylonitrile

[0121] The first unsaturated ester monomer: 80 parts of benzyl acrylate

[0122] The second polymer synthesis raw material of this embodiment includes the following components in parts by mass:

[0123] Second vinyl monomer: 43 parts of α-methylstyrene,

[0124] Second unsaturated ester monomer: 80 parts of butyl acrylate, 10 parts of ethyl (meth)acrylate

[0125] Unsaturated functional monomer: 13 parts of sorbic acid

[0126] Second monomer: 5 parts of N,N-dimethylacrylamide.

[0127] The preparation method of this embodiment is basically the same as that of Embodiment 1, except that, in the negative electrode binder, the mass ratio of the first polymer to the second polymer is 2:1.

[0128] Example 5

[0129] This embodiment is basically the same as embodiment 4, except that the unsaturated monomer is methyl sorbate.

[0130] Example 6

[0131] This embodiment is basically the same as Embodiment 1, except that the first polymer synthesis raw material of this embodiment comprises the following components in parts by mass:

[0132] First vinyl monomer: 30 parts of styrene, 15 parts of vinyl toluene

[0133] Aliphatic conjugated unsaturated monomer: 43 parts of 1,3-pentadiene

[0134] Conventional acidic monomer: 10 parts of methacrylic anhydride

[0135] Functional acid monomer: 5 parts of sorbic acid

[0136] The first unsaturated ester monomer: 70 parts of methyl acrylate.

[0137] Example 7

[0138] This embodiment is basically the same as Embodiment 1, except that the mass ratio of methacrylic anhydride to sorbic acid is 1:25.

[0139] Example 8

[0140] The second polymer synthesis raw material of this embodiment includes the following components in parts by mass:

[0141] Second vinyl monomer: 55 parts,

[0142] The second unsaturated ester monomer: 58 parts of 2-isooctyl acrylate

[0143] Unsaturated functional monomer: 2 parts of sorbic acid

[0144] Second monomer: 17 parts of N-methyl-2-acrylamide.

[0145] Comparative Example 1

[0146] This comparative example is basically the same as Example 1, except that benzoic acid is used in this comparative example to replace the sorbic acid in the first polymer synthesis raw material in Example 1.

[0147] Comparative Example 2

[0148] This comparative example is basically the same as Example 1, except that propyl p-hydroxybenzoate is used in this comparative example to replace the sorbic acid in the first polymer synthesis raw material in Example 1.

[0149] Comparative Example 3

[0150] This comparative example is basically the same as Example 1, except that sorbic acid in the first polymer synthesis raw material in Example 1 is omitted.

[0151] Comparative Example 4

[0152] This comparative example is basically the same as comparative example 3, except that the sorbic acid in comparative example 3 is replaced by benzoic acid.

[0153] Comparative Example 5

[0154] This comparative example is basically the same as Example 1, except that the methacrylic anhydride in Example 1 is omitted.

[0155] Test example

[0156] 1. Glass transition temperature test

[0157] A differential scanning calorimeter (Shanghai Qunhong Instrument Equipment Co., Ltd., model: DSC-100) was used to detect the glass transition temperature Tg of the negative electrode binder of the embodiment and the comparative example. The steps include: turning on high-purity nitrogen, setting the nitrogen flow rate to 0.5-0.6L / min, turning on the DSC power supply, and running the desktop. Set the temperature: -60°C, constant temperature for 10min, -60°C-80°C, heating rate 10K / min, after setting, put the prepared sample into the heating furnace, cover the furnace body protection cover, and add an appropriate amount of liquid nitrogen to the constant temperature tank. When the sample temperature reaches -60°C, run the test.

[0158] 2. The negative electrode binders including the embodiments and comparative examples were prepared into lithium ion batteries, and their low temperature cycle performance, corrosion resistance and rate performance were tested.

[0159] The preparation method of the negative electrode sheet includes: mixing 1.5% of the negative electrode binder, 96% of the negative electrode active material graphite, 1% of the negative electrode conductive agent conductive carbon black, and 1.5% of the thickener sodium carboxymethyl cellulose (CMC), adding deionized water for stirring, and preparing a negative electrode composition. Then, the negative electrode composition is coated on both surfaces of the negative electrode current collector Cu foil, and after drying, cold pressing, slitting and other processes, a negative electrode sheet is obtained.

[0160] The particle size of graphite, the negative electrode active material, is 20 μm.

[0161] The preparation method of the positive electrode sheet includes: adding 97.3% of positive electrode active material lithium iron phosphate, 1% of positive electrode conductive agent conductive carbon black, and 1.7% of positive electrode binder polyvinylidene fluoride to N-methylpyrrolidone and stirring to prepare positive electrode slurry. Then, the positive electrode slurry is coated on both surfaces of positive electrode current collector Al foil, and after drying, cold pressing, slitting and other processes, a positive electrode sheet is obtained.

[0162] Subsequently, the positive electrode sheet, isolation film (PE film), and negative electrode sheet are stacked in order, so that the isolation film is placed between the positive and negative electrodes to play an isolating role, and the electrode assembly is made. The electrode assembly is placed in an outer packaging, and commercially available electrolyte is injected and packaged. After that, a lithium-ion battery is obtained through processes such as liquid injection, formation, and exhaust.

[0163] 1) Low temperature performance

[0164] The battery was placed at room temperature (25°C), charged to 4.50V at a constant current of 1C, then charged to 4.50V at a constant voltage of 0.05C, then discharged to 3.0V at a discharge rate of 1C, and then fully charged at a rate of 0.5C, and the discharge capacity Q of the 1C cycle was recorded. After the fully charged battery was stored at -20°C for 4 hours, it was discharged to 3.0V at a discharge rate of 1C, and the 1C discharge capacity Q1 was recorded. The low-temperature discharge capacity retention rate of the battery was calculated by the following formula, and the specific results are shown in Table 1.

[0165] Low temperature storage capacity retention rate (%) = Q1 / Q×100%

[0166] 2) Rate performance

[0167] The battery was charged and discharged at 25°C using a battery charge and discharge tester. The charge and discharge regime was as follows: 0.2C constant current charging to 4.25V, then switching to 4.25V constant voltage charging until the current decreased to 0.02C, after standing for 5 minutes, 0.2C constant current discharging to 2.5V, and recording the discharge capacity Q0.2c; after standing for 5 minutes, 0.2C constant current charging to 4.25V, then switching to 4.25V constant voltage charging until the current decreased to 0.02C, after standing for 5 minutes, 3C constant current discharging to 2.5V, and recording the discharge capacity Q3c. The capacity retention rate can be calculated according to the following formula. The specific results are shown in Table 1.

[0168] 3C discharge rate capacity retention rate = Q3c / Q0.2c×100%

[0169] 3) Anti-corrosion test

[0170] The negative electrode binders prepared in the examples and comparative examples were placed in a cool place at room temperature for 14 days to observe whether mold spots appeared. The specific results are shown in Table 1.

[0171] 4) Electrolyte mass swelling rate test

[0172] Take two containers and add electrolyte, the electrolyte is 1M LiPF6, the polymer particles are made into a film and dried to bear weight to obtain Winitial, the film specification is a circular sheet with a diameter of 20mm and a thickness of 20μm, the polymer particles are immersed in the electrolyte, after leaving for 72h, take out and wipe off the electrolyte on the surface and weigh to obtain Wbalance, swelling degree = (Wbalance-Winitial) / Winitial*100%, the specific results are shown in Table 1.

[0173] Table 1

[0174]

[0175] It can be seen from the test results in Table 1 that the negative electrode binder provided by the present invention has an excellent anti-corrosion effect and is beneficial to improving the low temperature performance and rate performance of the battery.

[0176] By comparing the test results of Example 1 and Comparative Example 1, Comparative Example 2 and Comparative Example 5, it can be seen that when the functional acidic monomer in the synthetic raw material monomer of the first polymer is not the monomer disclosed in the present invention, it cannot have a good anti-corrosion effect, and will cause the low temperature performance and rate performance of the battery to decline; and when the synthetic raw material monomer of the first polymer does not contain conventional acidic monomers, it will also fail to have a good anti-corrosion effect, and will cause the low temperature performance and rate performance of the battery to decline.

[0177] By comparing Example 1 and Comparative Example 3, it can be seen that when the synthetic raw material monomer of the first polymer of the negative electrode binder does not contain a functional acidic monomer, the anti-corrosion performance, low temperature performance and rate performance of the negative electrode binder are significantly reduced; by comparing Comparative Example 3 and Comparative Example 4, it can be seen that when the synthetic raw material monomer of the first polymer does not contain a functional acidic monomer, if the unsaturated functional monomer in the synthetic raw material monomer of the second polymer is not a preferred monomer of the present invention, the low temperature performance and rate performance of the battery will be further reduced.

[0178] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A negative electrode binder, characterized in that: The negative electrode binder includes a first polymer and a second polymer located on the surface of the first polymer; The first polymer comprises a first vinyl monomer unit, an aliphatic conjugated unsaturated monomer unit, a first unsaturated carboxylic acid monomer unit, and a first unsaturated ester monomer unit, wherein the weight ratio of the first vinyl monomer unit, the aliphatic conjugated unsaturated monomer unit, the first unsaturated carboxylic acid monomer unit, and the first unsaturated ester monomer unit is 0.1-50: 0.1-50: 0.1-20: 0.1-100; The second polymer comprises a second vinyl monomer unit, a second unsaturated ester monomer unit and an unsaturated functional monomer unit; the weight ratio of the first vinyl monomer unit, the second vinyl monomer unit, the second unsaturated ester monomer unit and the unsaturated functional monomer unit is 0.1-50:20-100:20-100:0.1-20; The first unsaturated carboxylic acid monomer unit includes a conventional acid monomer unit and a functional acid monomer unit, wherein the functional acid monomer unit includes at least one of sorbic acid and dehydroacetic acid, and the conventional acid monomer unit includes at least one of acrylic acid or anhydride unit, methacrylic acid or anhydride unit, fumaric acid or anhydride unit, maleic acid or anhydride unit, itaconic acid or anhydride unit, and citraconic acid or anhydride unit; The mass ratio of the first polymer to the second polymer is 100:(0.01-50); The glass transition temperature of the negative electrode binder is -50 to 80° C.; the swelling rate of the negative electrode binder in 1M LiPF6 electrolyte is 50% to 300%.

2. The negative electrode binder according to claim 1, characterized in that The weight ratio of the conventional acidic monomer units to the functional acidic monomer units is 0.1-19.9:0.1-19.

9.

3. The negative electrode binder according to claim 1, characterized in that The first polymer further comprises a first monomer unit; The first monomer unit includes at least one of a (meth)acrylonitrile monomer unit, a vinyl pyrrolidone monomer unit, a butenyl nitrile monomer unit, and a vinyl ether monomer unit.

4. The negative electrode binder according to claim 3, characterized in that The weight ratio of the first monomer unit to the first vinyl-based monomer unit is 0.1-50:0.1-50.

5. The negative electrode binder according to claim 2, characterized in that: The second polymer further comprises a second monomer unit; The second monomer unit includes (meth)acrylonitrile unit, vinyl pyrrolidone unit, butenyl nitrile unit, vinyl ether unit, methacrylamide unit, diacetone acrylamide unit, ethyl acetoacetate methacrylate unit, N-hydroxymethyl methacrylamide unit, N,N-dimethylacrylamide unit, N-methyl-2-acrylamide unit, N-tert-butylacrylamide unit, 2-acrylamido-2-methylpropanesulfonic acid unit, dipropylene glycol diacrylate unit, triethylene glycol di(meth)acrylate unit At least one of the following units: polyethylene glycol 200 diacrylate units, polyethylene glycol 300 diacrylate units, polyethylene glycol 400 diacrylate units, polypropylene glycol 400 diacrylate units, tetraethylene glycol dimethacrylate units, polyethylene glycol 200 dimethacrylate units, polyethylene glycol 400 dimethacrylate units, trimethylolpropane triacrylate units, 2-(ethoxy)trimethylolpropane triacrylate units, pentaerythritol triacrylate units, and pentaerythritol tetraacrylate units.

6. A negative electrode sheet, characterized in that: The negative electrode sheet comprises the negative electrode binder according to any one of claims 1 to 5.

7. A lithium ion battery, characterized in that: The lithium-ion battery comprises the negative electrode binder according to any one of claims 1 to 5, or the negative electrode sheet according to claim 6.

Citation Information

Patent Citations

  • Polymerizable composition and dental material

    CN102648216A

  • Electrolyte for electricity storage device containing α,β-conjugated carboxylic acid

    JP2016189378A